Glycine Ameliorates Endoplasmic Reticulum Stress Induced by Thapsigargin in Porcine Oocytes - Yu, Sicong; Gao, Lepeng; Zhang, Chang; Wang, Yumeng; Lan, Hainan; Chu, Qianran; Li, Suo; Zheng, Xin (Frontiers in Cell and Developmental Biology, 2021)
Abstract The endoplasmic reticulum (ER) is a multifunctional organelle in the cytoplasm that plays important roles in female mammalian reproduction. The endoplasmic reticulum and mitochondria interact to maintain the normal function of cells by maintaining intracellular calcium homeostasis. As proven by previous research, glycine (Gly) can regulate the intracellular free calcium concentration ([Ca2+]i) and enhance mitochondrial function to improve oocyte maturation in vitro. The effect of Gly on ER function during oocyte in vitro maturation (IVM) is not clear. In this study, we induced an ER stress model with thapsigargin (TG) to explore whether Gly can reverse the ER stress induced by TG treatment and whether it is associated with calcium regulation. The results showed that the addition of Gly could improve the decrease in the average cumulus diameter, the first polar body excretion rate caused by TG-induced ER stress, the cleavage rate and the blastocyst rate. Gly supplementation could reduce the ER stress induced by TG by significantly improving the ER levels and significantly downregulating the expression of genes related to ER stress (Xbp1, ATF4, and ATF6). Moreover, Gly also significantly alleviated the increase in reactive oxygen species (ROS) levels and the decrease in mitochondrial membrane potential (Δ m) to improve mitochondrial function in porcine oocytes exposed to TG. Furthermore, Gly reduced the [Ca2+]i and mitochondrial Ca2+ ([Ca2+]m) levels and restored the ER Ca2+ ([Ca2+]ER) levels in TG-exposed porcine oocytes. Moreover, we found that the increase in [Ca2+]i may be caused by changes in the distribution and expression of inositol 1,4,5-triphosphate receptor (IP3R1) and voltage-dependent anion channel 1 (VDAC1), while Gly can restore the distribution and expression of IP3R1 and VDAC1 to normal levels. Apoptosis-related indexes (Caspase 3 activity and Annexin-V) and gene expression Bax, Cyto C, and Caspase 3) were significantly increased in the TG group, but they could be restored by adding Gly. Our results suggest that Gly can ameliorate ER stress and apoptosis in TG-exposed porcine oocytes and can further enhance the developmental potential of porcine oocytes in vitro.